Racism And Its Effect In Green Book Film By Peter Parelly : Socilogical Approach - Wulandari, Wulandari; Efendi, Dedi; Afrillesa, Rini (Krinok:Jurnal Linguistik Budaya, 2024)
This research analyzes the types and effects of acts of racism that occur in the film Green Book. The purpose of this study is (1) to clarify the types of racism that appear in the "Green Book" film. (2) to find the effects of racism felt by the characters in the "Green Book" film. In this study the researcher used a descriptive qualitative method, which is a research method that finds basic answers about racism and types of racism and explains the effects caused by acts of racism on characters in the "Green Book" film using the sociological approach.The results of the study revealed several findings: There are 24 data found by the author, the data is divided into types and effects of racism, there are many acts of racism that occur in the film "Green Book" and have been grouped by type through the theory of Wilson E Charles (2005), these types include 15 data Overt/Individual Racism and 9 data Institutional Racism. The researcher also finds all the effects of each type found in the data, the effects found based on Allport's theory (1991) are Anticoutine with 4 data, Discrimination 18 data and Physical attack 2 data. These effects are obtained from racism that appears in the type in the Green Book film.The reseacher also found all the effects of each type found in the data, the effects found based on Allport's theory (1991) are Anticoutine, Discrimination, Physical attack. From all the data displayed by the researcher, it can be concluded that Overt/Individual Racism occurs more often in the movie "Green Book". And then followed by Institutional Racism. From the 24 data above, it can also be concluded that the effect of Discrimination is an effect that often appears in the movie "Green Book".